Does intravenous sildenafil clinically ameliorate pulmonary hypertension during perioperative management of congenital heart diseases in children? – A prospective randomized study - Sharma, Vipul Krishen (Ann Card Anaesth, 2015)
BACKGROUND: Pulmonary hypertension (PHT), if present, can be a significant cause of increased morbidity and mortality in children undergoing surgery for congenital heart diseases (CHD). Various techniques and drugs have been used perioperatively to alleviate the effects of PHT. Intravenous (IV) sildenafil is one of them and not many studies validate its clinical use. AIMS AND OBJECTIVES: To compare perioperative PaO(2) – FiO(2) ratio peak filling rate (PFR), systolic pulmonary artery pressure (PAP) – systolic aortic pressure (AoP) ratio, extubation time, and Intensive Care Unit (ICU) stay between two groups of children when one of them is administered IV sildenafil perioperatively during surgery for CHDs. MATERIALS AND METHODS: Patients with ventricular septal defects and proven PHT, <14 years of age, all American Society of Anesthesiologists physical status III, undergoing cardiac surgery, were enrolled into two groups – Group S (IV sildenafil) and Group C (control) – over a period of 14 months, starting from October 2013. Independent t-test and Mann–Whitney U-test were used to compare the various parameters between two groups. RESULTS: PFR was higher throughout, perioperatively, in Group S. PAP/AoP was 0.3 and 0.4 in Group S and Group C, respectively. In Group S, mean group extubation time was 7 ± 7.34 h, whereas in Group C it was 22.1 ± 10.6. Postoperative ICU stay in Group S and Group C were 42.3 ± 8.8 h and 64.4 ± 15.9 h, respectively. CONCLUSION: IV sildenafil, when used perioperatively, in children with CHD having PHT undergoing corrective surgery, improves not only PaO(2) – FiO(2) ratio and PAP – AoP ratio but also reduces extubation time and postoperative ICU stay.